2002
DOI: 10.1142/s0129055x02001119
|View full text |Cite
|
Sign up to set email alerts
|

Ground State Properties of the Nelson Hamiltonian: A Gibbs Measure-Based Approach

Abstract: The Nelson model describes a quantum particle coupled to a scalar Bose field. We study properties of its ground state through functional integration techniques in case the particle is confined by an external potential. We obtain bounds on the average and the variance of the Bose field both in position and momentum space, on the distribution of the number of bosons, and on the position space distribution of the particle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 19 publications
1
52
0
Order By: Relevance
“…See, apart from [14] mentioned above, the papers [1,3,21]. As for the massless confined model we refer the reader to [7,9,24,26,38].…”
Section: Non-relativistic Qed: An Overviewmentioning
confidence: 99%
“…See, apart from [14] mentioned above, the papers [1,3,21]. As for the massless confined model we refer the reader to [7,9,24,26,38].…”
Section: Non-relativistic Qed: An Overviewmentioning
confidence: 99%
“…Arai et al [3,4] and Betz et al [11] studied the absence of ground states of some model and Dereziński and Gérard [18], Hirokawa [23], and Lőrinczi [34] established that of the Nelson model. However, Arai [1] takes a non-Fock representation and then shows the existence of a ground state of H under (1.8).…”
Section: The Nelson Modelmentioning
confidence: 99%
“…In the present paper the soft boson means the boson in a ground state. Recently, the spectral properties of Nelson's Hamiltonian has been studied rather intensively (e.g., [2,9,11,16,20,24]). In particular, Betz et al showed in [9] that when the external potential is in the Kato class the total number of soft bosons for Nelson's Hamiltonian diverges under the infrared singularity (IRS) condition.…”
Section: §1 Introductionmentioning
confidence: 99%
“…Around the same time Lőrinczi et al showed in [24] that when the external potential is strongly confining there is no ground state of Nelson's Hamiltonian in spatial dimension 3. The results in both [9] and [24] are proved by means of functional integrals.…”
Section: §1 Introductionmentioning
confidence: 99%